2020
DOI: 10.1111/hsc.12973
|View full text |Cite
|
Sign up to set email alerts
|

Language and stigmatization of individuals with mental health problems or substance addiction in the Netherlands: An experimental vignette study

Abstract: Persons with mental health problems and/or substance addictions (MHPSA) are stigmatised more than persons with physical conditions. This includes stigmatisation by care professionals. Stigma is considered one of the most important barriers for recovery from these conditions. There is an ongoing debate that use of language can exacerbate or diminish stigmatisation. Therefore, we conducted an experiment examining how four different ways of referring to a person with (a) alcohol addiction, (b) drug addiction, (c)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 39 publications
0
6
1
Order By: Relevance
“…These findings are largely discordant with past literature, which has shown that noun labels both promote stigma (Granello & Gibbs, 2016; Penn & Nowlin-Drummond, 2001) and result from stigmatizing beliefs (Carnaghi et al, 2008; Howell et al, 2014; Howell & Woolgar, 2013) or low empathy (Howell et al, 2014; Krzyzanowski et al, 2019). Notably, however, some previous work has failed to find differences between person-first and noun labels (e.g., Martinelli et al, 2020), as in the current studies. While it is difficult to account for this discrepancy, it may be due in part to methodological differences.…”
Section: Discussioncontrasting
confidence: 79%
“…These findings are largely discordant with past literature, which has shown that noun labels both promote stigma (Granello & Gibbs, 2016; Penn & Nowlin-Drummond, 2001) and result from stigmatizing beliefs (Carnaghi et al, 2008; Howell et al, 2014; Howell & Woolgar, 2013) or low empathy (Howell et al, 2014; Krzyzanowski et al, 2019). Notably, however, some previous work has failed to find differences between person-first and noun labels (e.g., Martinelli et al, 2020), as in the current studies. While it is difficult to account for this discrepancy, it may be due in part to methodological differences.…”
Section: Discussioncontrasting
confidence: 79%
“…Other studies have shown that using person-first language to refer to individuals with MI results in higher levels of tolerance among professional counselors and community members (Granello & Gibbs, 2016;. These findings have also failed to replicate, suggesting that subtle differences in language may not impact stigmatizing attitudes about MI (Martinelli, 2020;Masland & Null, 2021;Nobel & Marson, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The American Psychological Association (APA) defines stigma as an individual’s negative perception of some specific characteristics of themselves or others that has an impact on physical and mental health and personal and social relations [ 8 ]. Several individual characteristics have been clearly defined as sources of stigma, such as being a minority [ 9 , 10 ], using different languages [ 11 , 12 ], living in lower socioeconomic environments [ 13 ], and being a substance abuser [ 14 – 17 ]. Having multiple such traits, for instance, being both a minority and substance abuser, increases the impact of stigma.…”
Section: Introductionmentioning
confidence: 99%